Pengaruh Brand Consciousness, Brand Awareness, Brand Nationality Terhadap Loyalitas Generasi Z yang Dimoderasi Brand Schematicity - Faizal Musthofa Zinka Ahmad Syah; Soepatini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of brand consciousness, brand awareness, and brand nationality on brand loyalty of Generation Z, with brand schematicity as a moderating variable. UNIQLO, as a fast fashion brand from Japan, was chosen because of its popularity in Indonesia, especially among Generation Z who are known to be technology-savvy, selective about brands, and oriented towards values and self-identity. This study uses a quantitative approach with a survey method of 101 Generation Z respondents in the Solo Raya area who have purchased UNIQLO products. The sampling technique is purposive sampling. Data analysis was carried out using SEM-PLS with the help of SmartPLS 3.0 software. The results of the study indicate that brand consciousness, brand awareness, and brand nationality have a positive and significant effect on brand loyalty. In addition, brand schematicity is proven to strengthen the relationship between the three variables and brand loyalty, indicating that individuals with high brand cognitive schemas tend to be more loyal to brands that match their personal image and values. The coefficient of determination (adjusted R²) value of 83.8% indicates that this model has high predictive power on brand loyalty. These findings provide theoretical contributions to the consumer behavior literature as well as practical implications for fashion brand marketing strategies. Companies are advised to prioritize emotional values and identity in brand communications to build stronger engagement with Generation Z consumers.